An economic analysis of a solar assisted heat pump system for cooling, water heating and drying - Hawlader, Mohammad Nurul Alam; Shaochun, Ye (2011)

(untitled)
A solar assisted heat-pump system has been developed to provide cooling, water heating and drying. The energy required for the system is met by a combination of energy collected from the sun, ambient and the energy recovered from a vapor compression heat-pump system, which also serves as an air-conditioner. The presence of evaporator-collector, which is in parallel connection with the room evaporator, enables the system to operate round the clock. Experiments and simulations were carried out to provide a better understanding of the system. Based on the validated simulation model, an economic optimization was performed to identify the best collector size for a given load and its distribution, using two methods, life cycle savings (LCS) and payback period. The load pattern is determined based on a typical small hotel with the air-con room area of 500m2, daily hot water demand of 18m3 and daily drying demand of 90kg. It is found that the life cycle saving method leads to the prediction of the optimum collector area of 55 m2. The analyses based on payback period, on the other hand, predicted an optimum collector area of 45 m2. The minimum payback period is about 1.5 years.